Trends in Rotavirus Laboratory Detections and Internet Search Volume Before and After Rotavirus Vaccine Introduction and in the Context of the Coronavirus Disease 2019 Pandemic—United States, 2000–2021 - Burnett, Eleanor; Parashar, Umesh D; Winn, Amber; Tate, Jacqueline E (The Journal of infectious diseases, 2022)
Abstract Background Since rotavirus vaccines became available in the United States in 2006, there have been reductions in rotavirus hospitalizations, changes in seasonality, and the emergence of a biennial trend of rotavirus activity. Reductions in other pathogens have been associated with coronavirus disease 2019 (COVID-19) mitigation measures. We assessed ongoing rotavirus disease trends during the COVID-19 pandemic. Methods We report a 3-week moving average of the number of rotavirus tests, positive tests, and the percent positivity from laboratories reporting to the National Respiratory and Enteric Virus Surveillance System (NREVSS) from July 2000 through June 2021. To complement NREVSS data, we analyzed Google internet search interest in “rotavirus” from July 2004 to June 2021. Results Declines in rotavirus activity following vaccine introduction and the biennial trend are evident through the 2018–2019 surveillance year. In 2019–2021, rotavirus test positivity was below the historic ranges during the months of typically high rotavirus activity, and precipitous declines were noted in March 2020. Conclusions In the 15 years since rotavirus vaccine was introduced, the number of laboratory-detected rotavirus infections has been consistently lower than during the prevaccine era. During the COVID-19 pandemic, rotavirus activity was suppressed. There may be many rotavirus-susceptible children during the 2021–2022 rotavirus season. Since rotavirus vaccine was introduced in the US, rotavirus infections have been consistently lower than during the prevaccine era. During the first 2 years of the COVID-19 pandemic, rotavirus detections declined even further. Rotavirus activity may rebound during the 2021–2022 season.